Adoption of reusable learning objects by postgraduate nursing students in Oman - Al-Hasni, Asiya (2022)
Background: E-learning offers innovative methods of education and is increasingly recognized as an advanced teaching strategy in healthcare education and lifelong learning, facilitating nurses’ continuous professional development. E-learning offers various solutions in higher education and nursing, but raises challenges in terms of the provision of high-quality materials, in terms of both content and media. Therefore, there is a need to explore the extent to which reuse of materials can be a successful strategy. This study explores how innovative technologies like reusable learning objects (RLOs) can support postgraduate nursing education in theory and clinical in Oman. Specifically, it explores the adoption of RLOs developed at the University of Nottingham (UK) for use in Oman Higher Institute of Health Specialities (HIHS). Aim: To explore the drivers of and barriers to the adoption of RLOs by postgraduate nursing students in Oman, to improve their knowledge, skills, and confidence.